Mobility and Entrepreneurship in Ecuador: A Pseudo-Panel Approach - Xavier Orde\~nana; Ramon Villa (Inter-American Development Bank (IDB), 2012)
Does entrepreneurship contribute to improving social mobility in Ecuador? This paper constructs a pseudo-panel to analyze the dynamic effect of entrepreneurship on Ecuadorian household incomes during the period 2002-2010. Using three estimation scenarios, the paper finds a significant level of unconditional mobility and an important effect of entrepreneurship (conditional mobility).
Keywords: J16; L26; M13; 330